Association between maternal anthropometry and birth weight in urban and rural areas of Pune, Maharashtra - RUTAMBHARA NHAWKAR; DEVAKI GOKHALE (International Journal of Pharma and Bio Sciences, 2018)
Birth weight is a predictor of neonate’s chances of survival, growth and long-term physical and psychosocial development. Low birth weight (LBW) is a major determinant of infant mortality and morbidity. There have not been many studies on maternal risk factors of LBW on a comparative basis between rural and urban areas The objective was to assess maternal anthropometry and its relation to birth weight of neonate in rural and urban areas of Pune. A follow- up study was conducted during November 2016 to April 2017. Purposive sampling technique was used to recruit urban (n=80) and rural (n=77) pregnant women and anthropometric measurements were recorded followed by interviewing them using questionnaires to obtain socio-demographic information. All the data were entered into SPSS package (version 23). Association of the maternal risk factors under study was assessed by applying t test and considering p value ≤0.05 statistically significant. Among n=157 pregnant women, (24.45%) were low birth weight neonates, (75.55%) had normal weight. The proportion of low birth weight was found greater in rural (37.7%) than urban (11.2%). There was a significant association between pre- pregnancy weight and pre- pregnancy BMI and its subsequent effect on birth weight (p<0.05) among pregnant women. Weight gain during 1st, 2nd and 3rd trimester had an impact on overall weight gain during pregnancy which in turn affected the birth weight of neonate. Women who delivered low birth weight neonates were of short stature (p<0.05) compared to those women who had delivered normal weight neonates. Besides, maternal nutrition, low socio-economic status, and maternal anthropometry (height, pre-pregnancy weight, BMI) had impact with birth weight of neonates.